Mechanisms of Action of Fruit and Vegetable Phytochemicals in Colorectal Cancer Prevention (2023)
ABSTRACT: Colorectal cancer (CRC) is the third most common cancer worldwide and its incidence is expected to increase by almost 80% by 2030. CRC apparition is related to poor diet, mainly due to low consumption of phytochemicals present in fruits and vegetables. Hence, this paper reviews the most promising phytochemicals in the literature, presenting scientific evidence regarding potential CRC chemopreventive effects. Moreover, this paper reveals the structure and action of CRC mechanisms that these phytochemicals are involved in. The review reveals that vegetables rich in phytochemicals such as carrots and green leafy vegetables, as well as some fruits such as pineapple, citrus fruits, papaya, mango, and Cape gooseberry, that have antioxidant, anti-inflammatory, and chemopreventive properties can promote a healthy colonic environment. Fruits and vegetables in the daily diet promote antitumor mechanisms by regulating cell signaling and/or proliferation pathways. Hence, daily consumption of these plant products is recommended to reduce the risk of CRC.